2020
DOI: 10.1002/ece3.5975
|View full text |Cite
|
Sign up to set email alerts
|

Integrating broad‐scale data to assess demographic and climatic contributions to population change in a declining songbird

Abstract: Climate variation and trends affect species distribution and abundance across large spatial extents. However, most studies that predict species response to climate are implemented at small spatial scales or are based on occurrence‐environment relationships that lack mechanistic detail. Here, we develop an integrated population model (IPM) for multi‐site count and capture‐recapture data for a declining migratory songbird, Wilson's warbler (Cardellina pusilla), in three genetically distinct breeding populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 75 publications
(128 reference statements)
0
14
0
Order By: Relevance
“…To determine the vulnerability of populations to changing environmental conditions, it is critical to link vital rates to ecological covariates that will be impacted by global change (Saracco & Rubenstein, 2019). Our IPM-BPVA revealed that (a) climate affects loon population dynamics via both reproduction and adult survival, (b) interactions between different climate variables result in complex patterns of population dynamics such that the effects of climatic conditions may take multiple years to become apparent in a long-lived, high-trophic level species (Crespin et al, 2006;Salvidio et al, 2016) and ( Northrup et al, 2019;Sohl, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the vulnerability of populations to changing environmental conditions, it is critical to link vital rates to ecological covariates that will be impacted by global change (Saracco & Rubenstein, 2019). Our IPM-BPVA revealed that (a) climate affects loon population dynamics via both reproduction and adult survival, (b) interactions between different climate variables result in complex patterns of population dynamics such that the effects of climatic conditions may take multiple years to become apparent in a long-lived, high-trophic level species (Crespin et al, 2006;Salvidio et al, 2016) and ( Northrup et al, 2019;Sohl, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of apparent breeding success as indicated by the LTRE (Fig. 2) must be treated with some care, as it is known that latent variables often seem to explain large proportions of the growth rates (Ahrestani et al 2017, Saracco and Rubenstein 2020), potentially because they may absorb systematic bias associated with the different datasets (Tavecchia et al 2009, Taylor et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies were explicitly designed to aid in biodiversity conservation (Hudson et al, 2017; Rosenberg et al, 2017). For the same reason, BBS data have often been used as a yardstick for evaluating the performance of new modeling tools in ecology (Link et al, 2020; Saracco & Rubenstein, 2020; Valle et al, 2018) and conservation (Cam, Nichols, Sauer, et al, 2002; Polasky et al, 2001), as well as for testing general concepts and theories of community ecology such as the scaling of population variability (Keitt & Stanley, 1998), the species pool hypothesis (Cam et al, 2000), biotic homogenization (Martin et al, 2017; Sorte & McKinney, 2007), abundance–occupancy relationships (Zuckerberg, Porter, et al, 2009), area‐heterogeneity trade‐off (Chocron et al, 2015), the insurance hypothesis (Valone & Barber, 2008), diversity–stability relationships (Catano et al, 2020), and many more (Bertuzzo et al, 2011; Hansen et al, 2011; Maurer et al, 2013; McGill, 2003; Mikkelson et al, 2011; Mimet et al, 2019; Osorio‐Olvera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%